ANALISIS KETERSEDIAAN DAN KEBUTUHAN AIR BAKU PADA EMBUNG SUNGAI BILAL KABUPATEN NUNUKAN MENGGUNAKAN METODE F.J. MOCK - Nurdiansyah, Nurdiansyah; Faizal, Rahmat; Amiruddin, Aswar (Civil Engineering Scientific Journal, 2023)
ABSTRACT : Due to population growth and the region's fast development, domestic and non- domestic water consumption has grown in Nunukan Regency. To meet the clean water demand, the government has built the Bilal River Reservoir, which initiated a study of the Bilal River Reservoir to be carried out to determine the reservoir's reliability in meeting the demand for clean water in line with population growth. This study analyzed water availability and the demand for raw water in the Bilal River Reservoir. In the analysis of water availability, the Modified Penman approach is used to analyze evapotranspiration, while the F.J. Mock method was used to study effective debit. From the analysis of raw water availability using the F.J. Mock with 90% reliability, The biggest Q90 was in January at 119 liters/sec, and the smallest was in December at 15 liters/sec. As well as the results of the largest water demand analysis in 2031 in the West Nunukan Village zone of 19,947 liters/sec and the smallest in 2022 in the Central Nunukan Village zone of 6,249 l/s.Keywords: Bilal River Reservoir, Water Availability, Water Demand, F.J. Method Mock ABSTRAK: Meningkatnya aktivitas penduduk ditambah dengan berkembangnya pembangunan yang semakin pesat menyebabkan kebutuhan air untuk domestik maupun non domestik yang meningkat di Kabuapten Nunukan. Dalam rangka upaya pemenuhan kebutuhan air bersih, pemerintah Kabupaten Nunukan membangun Embung Sungai Bilal. Kajian terhadap Embung Sungai Bilal perlu dilakukan untuk mengetahui keandalan embung dalam memenuhi kebutuhan air bersih sejalan dengan pertumbuhan penduduk. Penelitian ini bertujuan untuk menganalisis ketersediaan air dan kebutuhan air baku pada Embung Sungai Bilal. Pada analisis ketersediaan air perhitungan Evapotranspirasi menggunakan metode Penman Modifikasi dan Debit Efektif menggunakan metode F.J. Mock. Dari hasil analisis ketersediaan air baku dengan menggunakan metode F.J. Mock dengan keandalan 90%. Q90 terbesar pada bulan Januari sebesar 119 ltr/dtk terkecil pada bulan Desember sebesar 15 ltr/dtk. Serta hasil analisis kebutuhan air terbesar pada tahun 2031 zona Kelurahan Nunukan Barat sebesar 19,947 lt/dtk, terkecil pada tahun 2022 zona Kelurahan Nunukan Tengah sebesar 6,249 lt/dtk.Kata kunci: Embung Sungai Bilal, Ketersediaan Air, Kebutuhan Air, Metode F.J. Mock